2008
DOI: 10.1038/ki.2008.378
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Spry-1, an inhibitor of GDNF/Ret, causes angiotensin II-induced ureteric bud branching

Abstract: Mutations of the renin-angiotensin system (RAS) genes are associated with congenital abnormalities of the kidney and urinary tract. We have shown that angiotensin (Ang) II stimulates ureteric bud (UB) branching in vitro. The present study tested the hypothesis that Ang II stimulates the GDNF/c-Ret/Wnt11 pathway. E12.5 mice metanephroi were grown for 24 hours in the presence or absence of Ang II or AT1R receptor antagonist candesartan and subjected to whole-mount ISH. c-Ret, a receptor tyrosine kinase for GDNF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 37 publications
(58 reference statements)
1
62
0
1
Order By: Relevance
“…Spatial distribution of ACE2 immunoreactivity during gestation shifts from diffuse staining in the UBs, nascent glomeruli, and the mesenchyme on E12.5 to a more localized expression in the tubular epithelia that resemble morphologically proximal tubules during E14.5-E18.5. We have recently reported that Ang II, when applied directly to whole intact E11.5 mouse metanephroi cultured in vitro, stimulates UB branching (18). The presence of ACE2 in the UB branches suggests a novel role for ACE2 in the regulation of UB morphogenesis.…”
Section: Ontogeny Of Ace2mentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial distribution of ACE2 immunoreactivity during gestation shifts from diffuse staining in the UBs, nascent glomeruli, and the mesenchyme on E12.5 to a more localized expression in the tubular epithelia that resemble morphologically proximal tubules during E14.5-E18.5. We have recently reported that Ang II, when applied directly to whole intact E11.5 mouse metanephroi cultured in vitro, stimulates UB branching (18). The presence of ACE2 in the UB branches suggests a novel role for ACE2 in the regulation of UB morphogenesis.…”
Section: Ontogeny Of Ace2mentioning
confidence: 99%
“…Although all ACE2-mutant lines were generated with randomly mixed genetic backgrounds derived from C57BL/6 and 129 mice (11,15,16), the differences in cardiac structure and function, the dominant phenotype reported in ACE2-null adult mice (11), do not appear to be due to variability in genetic background (17). Because we have previously reported an important role for Ang II and its AT 1 R in ureteric bud (UB) morphogenesis during embryonic kidney development in CD1 mice (18), we chose to examine ACE2 ontogeny in CD1 mice.…”
Section: Developmental Changes In Ace2 Gene Expressionmentioning
confidence: 99%
“…Organs were homogenized in cold lysis buffer containing a cocktail of enzyme inhibitors (35). The samples were centrifuged, and the supernatants containing proteins (40 µg/lane) were resolved on 10% sodium dodecyl sulfate-polyacrylamide gels and transferred to nitrocellulose membranes.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…SYBR Green quantitative real-time RT-PCR with (P)RR-specific primers (SABiosciences, Frederick, MD) was conducted as described previously (35). The quantity of (P)RR mRNA expression was normalized to that of glyceraldehyde 3-phosphate dehydrogenase mRNA expression.…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation